HOW DOES SOCIAL MEDIA MARKETING THROUGH CELEBGRAM PROMOTION AFFECT THE GROWTH OF MSMES IN INDONESIA? - Hamdalah, Nurul; Setiowati, Nur Eka; Wartoyo, Wartoyo (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this study is to determine whether or not there is an effect of marketing costs on net profit with sales volume as an intervening variable in culinary and fashion businesses in the Cirebon City area that use celebrity promotion services. This research uses field research (Field Research) with a quantitative approach. For data collection techniques carried out, namely through questionnaires. The population in this study is all culinary and fashion business actors in the Cirebon City area with a sampling technique using probability sampling, namely with a simple random method, which is as many as 44 business actors. The test tool used in this study is with path analysis techniques using the help of IBM Statistic SPSS software version 26. Based on the results of the channel analysis carried out, the results were obtained: (1) Marketing cost variables do not have a direct effect on net income, (2) Marketing cost variables have a direct and positive effect on sales volume, (3) Sales volume variables have a direct and positive effect on net income, (4) Indirect marketing cost variables through sales volume have a positive effect on net profit.